GAMBARAN TINGKAT KECEMASAN IBU HAMIL TERHADAP TERPAPARNYA COVID-19 MENJELANG PROSES PERSALINAN - Mita Nur Azizah, - (2021)
ABSTRACT Mita Nur Azizah (NIM 1806922). Overview Of Pregnant Woment's Anxiety Level Against Exposure To COVID-19 Ahead Of Childbirth Scientific Paper Diploma III Nursing University of Education Indonesia in Sumedang, University of Education Indonesia, 2021. This research is based on the ongoing COVID-19 pandemic. The increasing spread of coronavirus outbreak makes many people experience anxiety including pregnant women. Anxiety is a feeling of unease because it is uncomfortable. Anxiety can strengthen individuals to take action to avoid threats, or referred to as maladaptive responses to something that causes fear and worry so as to cause adverse effects for pregnant women, especially in the III trimester. The purpose of this study is to find out the level of anxiety that pregnant women feel towards exposure to COVID-19 ahead of childbirth. The method used in this study was descriptive research method with quantitative approach. The samples involved in this study were 35 pregnant women who met the criteria and determined using purposive sampling techniques in their sampling. The instruments used in this study are the Perinatal Anxiety Screening Scale (PASS) totaling 31 statement points with four answer options. The research results show that pregnant women in the III trimester with parity status primigravida and multigravida in the working area of Puskesmas Conggeang, during the COVID-19 pandemic and before childbirth experienced anxiety with a category of mild to severe. The conclusion is that pregnant women on average feel moderate anxiety. More research is needed on how to overcome anxiety during the COVID-19 pandemic specifically in pregnant women. Keywords: Anxiety, Pregnant Women, COVID-19, Childbirth